Versatile approach to densely substituted isoxazolines and pyrazolines: Focus on a quaternary carbon center as a constitutive feature. Issue 23 (4th June 2020) - Abdelli, Abderrahmen; Gharsa, Haythem; Jmaï, Momtez; Gaucher, Anne; Efrit, Mohamed Lotfi; M'rabet, Hedi; Prim, Damien
Graphical abstract: Highlights: Synthesis of isoxazolines and pyrazolines from a common allylphosphonate starting material. Easy access to C5 quaternary carbon center. Selective 1, 3-dipolar cycloaddition under mild conditions. Specific antibacterial activity against Staphylococcus aureus strain. Abstract: A new family of isoxazolines has been obtained via 1, 3-dipolar cycloaddition in good to high yields under mild conditions. Our approach focused on construction of the heterocyclic ring and direct access to a quaternary carbon center at position 5. The methodology has also been extended to pyrazoline analogues. The antibacterial activity of these compounds was evaluated, showing specific antibacterial activity against Staphylococcus aureus . Six members of these heterocycles exhibited MIC values of 4 µg/mL.